Geopolymer composites for chemical looping combustion. (1st August 2018) - Miccio, F.; Bendoni, R.; Piancastelli, A.; Medri, V.; Landi, E.
Graphical abstract: Abstract: Chemical looping combustion allows a simple separation of CO2 during the combustion of fossil fuels, thanks to the use of regenerable oxygen carriers. In this work, novel materials containing manganese and iron/manganese oxides have been developed via geopolymerization, and characterized in thermogravimetric apparatus and fixed bed reactor. The materials demonstrated suitable characteristics for chemical looping combustion (CLC). The tests conducted in the temperature range 800–900 °C revealed the good performance of the developed oxygen carriers, which also exhibited the ability to release O2 in inert conditions. Efficiencies in CO conversion up to 99% were achieved, as well as some synergies between Fe and Mn oxides gave a beneficial effect toward the oxygen yield. X-ray diffraction analyses of the samples confirmed the effective reduction/oxidation behavior of the materials, as well as the morphological characterization did not reveal dramatic changes of the internal microstructure up to 900 °C.